Assessment of angiogenesis in children with acute lymphoblastic leukemia based on serum vascular endothelial growth factor assay - Agnieszka Mizia-Malarz; Grazyna Sobol-Milejska (Indian Journal of Medical and Paediatric Oncology)
Introduction: Vascular endothelial growth factor A (VEGFA) is a key proangiogenic cytokine. The role of angiogenesis in acute lymphoblastic leukemia (ALL) is still unclear. The purpose of the study was to assess angiogenesis in children with ALL based on serum VEGFA level determined at diagnosis and at remission with further participant subdivision into different risk groups. Materials and Methods: Forty children, aged 3–12 years (mean age: 8 years) with newly diagnosed ALL, were enrolled in the study. The control group (Group C) was twenty healthy children. According to the risk assessment, they were classified into a standard-risk group, an intermediate-risk group (IRG), or a high-risk group (HRG). Results: The median serum VEGFA levels at diagnosis were significantly higher in IRG and HRG as compared to Group C. The VEGFA levels at remission were significantly higher in all study groups, as compared to Group C. The differences in median values of serum VEGFA levels between the study groups both at diagnosis and at remission were not statistically significant. Conclusions: The angiogenesis in ALL seems to be intensified at diagnosis as a result of neoplasmatic bone marrow rebuilding and at remission as its intensive recovering.